2010
DOI: 10.1016/j.exer.2010.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Differential susceptibility to experimental glaucoma among 3 mouse strains using bead and viscoelastic injection

Abstract: The purpose of this experiment was to test the susceptibility to retinal ganglion cell (RGC) axon loss and RGC layer cell loss from experimental glaucoma among 3 mouse strains, and between younger and older mice. We obstructed the mouse aqueous outflow channels by injecting 2 μL of 6 μm diameter, polystyrene beads followed by 3 μL of viscoelastic solution into the anterior chamber with a glass micropipette. We evaluated intraocular pressure (IOP) and damage to RGC as measured by optic nerve axon counts and RGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
153
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(173 citation statements)
references
References 31 publications
17
153
2
1
Order By: Relevance
“…In previous reports, we have shown that the Aca23 mutants, which had the greatest permeability estimates here, are the strain that is most resistant to glaucoma damage, while the CD1 mice with lowest permeability are most susceptible to glaucoma injury, with the B6 mice intermediate in both measures. [31][32][33] This finding lends further credence to the potential role of the state of the sclera as a factor in glaucoma susceptibility. In addition, there was a significant, monotonic decrease in scleral permeability with greater glaucoma damage in experimental mice in this study.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In previous reports, we have shown that the Aca23 mutants, which had the greatest permeability estimates here, are the strain that is most resistant to glaucoma damage, while the CD1 mice with lowest permeability are most susceptible to glaucoma injury, with the B6 mice intermediate in both measures. [31][32][33] This finding lends further credence to the potential role of the state of the sclera as a factor in glaucoma susceptibility. In addition, there was a significant, monotonic decrease in scleral permeability with greater glaucoma damage in experimental mice in this study.…”
Section: Discussionmentioning
confidence: 57%
“…1,12,20,29 Chronically elevated IOP in mice leads to decreases in nonfibrillar scleral elements, alterations in collagen lamellar orientation, a decrease in collagen fibril diameter, and increased cell division with a transition to the myofibroblast phenotype in scleral fibroblasts (Oglesby EN, unpublished observations, Copyright 2014 The Association for Research in Vision and Ophthalmology, Inc. www.iovs.org j ISSN: 1552-5783 2013). 16 Aca23 mice (mice of B6 background that are homozygous for mutation in collagen 8a2) are significantly protected against injury from experimental glaucoma, 30,31 while CD1 mice are considerably more susceptible to damage than B6 mice 32 and differ in important features of scleral anatomy and response. 9,33 Experimental glaucoma in mice increases axial length and width by 6% to 10%, with thinning of the peripapillary sclera and increased scleral stiffness in mechanical inflation testing.…”
mentioning
confidence: 99%
“…The estimated increase in RGC loss in glaucoma is strongly supported by experimental data. 48,49 Assuming that early visual field defects may be identified after a loss of B40% of RGCs, this equates to an approximate 10-year delay in the detection of abnormalities by standard perimetry. 8 Quigley et al, 3 reported that in monkeys, 4-13% of all RGCs were undergoing apoptosis in the 2-4 weeks immediately following experimentally induced glaucoma, with sustained IOP giving rise to a prevalence of 1% RGC apoptosis.…”
Section: Presence Of Retinal Ganglion Cell Apoptosis In Glaucomamentioning
confidence: 99%
“…The goal of any experimental procedure to elevate the IOP is to inhibit aqueous humour outflow without interfering with the eye's ability to produce this humour. There are four main approaches, scarring the anterior angle chamber by hypertonic saline injection (rats, Johnson et al, 1996;Morrison et al, 1997;mice, Kipfer-Kauer et al, 2010) laser photocoagulation (rats and mice, Salinas-Navarro et al, 2009a, 2010, venous cautery (Shareef et al, 1995) and injection of microbeads in the anterior chamber (mice, Cone et al, 2010;Chen et al, 2011;rats and mice, Sappington et al, 2010). Laser photocoagulation, a method first described in monkeys (Gaasterland & Kupfer, 1974) and later in rats (Ueda et al, 1998), is based on the photocoagulation of the trabecular mesh alone or in combination with episcleral veins and/or perilimbar vessels Levkovitch-Verbin et al, 2007;Salinas-Navarro et al, 2009a, 2010.…”
Section: Inducedmentioning
confidence: 99%